Pengaruh Pendidikan Dan Pelatihan Kepemimpinan Terhadap Kinerja Aparatur Di Lingkungan Pemerintah Kabupaten Rokan Hulu - Gustia Hendri; Lilis Suryani (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2020)
Many factors can affect a person's performance, one of which is Education and training (Diklat). Training is a learning process in an organization that leads to changes in employee attitudes and behavior in order to meet expectations of work qualifications and demands for organizational development both internal and external. Among the types of education and training according to Government Regulation No. 14 of 1994 concerning Education and Training of Civil Servants, the author intends to examine leadership education and training that are classified in technical education and training. The main objective of this research is to find out and analyze the influence of leadership education and training on the performance of the apparatus in the government of Rokan Hulu Regency. This study examines the effect of Leadership Education and Training by using indicators of Training Implementation, Training Costs, Training Participants and Training Facilities on Apparatus Performance with indicators of Service Quality, Communication, Speed, Ability, and Initiatives. This type of research used in this study is this research using an associative explanatory approach (explanatory associate research) which seeks to explain the causal relationship between variables (associative) through hypothesis testing. The research method used is quantitative that aims to obtain evidence of a causal relationship or influence of the research variables. The total sample population in this study was 94 people with 2 people as key informants with census techniques for sampling, the type of data used was primary data collected by questionnaire and interview techniques while secondary data was collected by observation and documentation techniques. The data analysis technique used is the validity test, reliability test, normality test, simple linear regression test and partial test (T test). based on analysis techniques Based on the value that tcount is 10,587 at ttable with df = 92 and a significant level of 5% or 0.05 obtained 0.1707. Because tcount (10,587)> ttable (0.1707) then Ho is rejected and Ha is accepted, meaning that the variable Education and Training Leadership (X) has a significant influence on the Performance of the State Civil Apparatus (Y).